UNC System Smoke-Free Campus Initiative - Foster, Ally (East Carolina University, 2021)
The state of North Carolina is one of the leading producers of tobacco in the United States. As such, the tobacco industry has played a significant role in North Carolina politics for decades. The relationship between big tobacco companies and the state legislature has resulted in a restrictive policy for University of North Carolina System schools. General Statute 143, Article 64, Sections 595-601 establish that UNC System schools cannot restrict campus tobacco use farther than 100 feet from buildings, with the exception of health science campuses. Originating in Honors 2000, our group has conducted collaborative research to advocate for legislative change for over a year. Now, with support from the Student Government Association at East Carolina University, the ECU Faculty Senate, and the statewide Association of Student Governments, we are well-positioned to amend the current legislation. Our proposed bill amendment has also gained approval from Representative Kandie Smith and Representative Donna White, who will act as sponsors to advance our bill through the North Carolina General Assembly.
Keywords: smoke-free, tobacco